Hippopotamidae (Cetartiodactyla, Hippopotamoidea) from Kanapoi, Kenya, and the taxonomic status of the late early Pliocene hippopotamids from the Turkana Basin. Issue 140 (March 2020) - Boisserie, Jean-Renaud
Abstract: New hippopotamid specimens recently collected at Kanapoi (ca. 4 Ma) are similar to the taxon previously recognized in this site and referred to aff. Hippopotamus protamphibius . Their examination provided the opportunity to reassess the taxonomic status of this taxon. It appears different from the late Miocene hippopotamids from the Turkana Basin (prominently Archaeopotamus harvardi ), but also differs from the late Pliocene–early Pleistocene aff. Hip. protamphibius, which is smaller and displays more advanced features (notably canine expansion and orbit elevation). In contrast, the Kanapoi material appears very similar to the material from the Hadar Formation (3.4 Ma–2.9 Ma). However, the current confusion surrounding the taxonomic status of the Hadar specimens, previously attributed to various taxa that may be identical, does not allow attribution of a specific name to the Kanapoi material for now and, while waiting for the revision of Hadar hippopotamid diversity, it is referred here to aff. Hippopotamus cf. sp. Hadar. This contribution allows recognizing that a large hippopotamid, possibly a transitional form between the late Miocene species and Plio-Pleistocene species, was distributed from Afar to Turkana between 4.2 Ma and 2.95 Ma. The marked endemism of hippopotamids in the Pleistocene rift basins therefore initiated after 2.9 Ma.